'Now the Letters are All Back to Front and Upside Down': Teaching and Learning in the Context of Life‐Threatening Illness. (5th July 2021) - Morgan, Emily
Abstract : This paper considers education in the context of life‐threatening illness from a psychoanalytic perspective and is an edited and shortened version of a dissertation written for a Master's Degree in Psychoanalytic Observational Studies. Informed by the Work Discussion module, this paper uses observational material of a single case study during the author's time working as a learning mentor in a hospital school. The case study, with its participant observation method, considers the complexity of engaging a 4‐year‐old girl in learning while she undergoes treatment for cancer. The defences this child used against anxiety, such as a muscular rigidity as a form of protection against the trauma she was experiencing, will be explored. The author also suggests that with the consistent daily presence and available mind of the observer/mentor, who was able to think about Poppy's experience, the child began to let go of her 'second‐skin' defences and showed the beginnings of an interest in learning. The way in which the staff group struggle to manage the intense anxieties stirred up by their everyday work will also be discussed.